2016
DOI: 10.23953/cloud.ijalis.215
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Library and Information Services in Selected University Libraries in Africa

Abstract: The demands of modern information handling coupled with the advent of information and communication technology (ICT), which brings various competitors in information service delivery, demands an innovative approach from university libraries in reaching out to users, of which marketing is beneficial. This paper examines the strategies used by university libraries in Africa to market their resources and services to users and the problems experienced. The survey research design was adopted for this study. A quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…The application of Information and communication technology (ICT) is revolutionising library operations to leave the customers sufficiently satisfied. Edewor, Okite-Amughoro, Osuchukwu, and Egreajena (2016), in their contributions, state that the need for marketing library products and services was adopted due to the rapid explosion of information, the ICT revolution, the decline in reading attitudes and behaviour, the complexity of information, and the competitive environment in which libraries were no longer the only providers of information 15 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application of Information and communication technology (ICT) is revolutionising library operations to leave the customers sufficiently satisfied. Edewor, Okite-Amughoro, Osuchukwu, and Egreajena (2016), in their contributions, state that the need for marketing library products and services was adopted due to the rapid explosion of information, the ICT revolution, the decline in reading attitudes and behaviour, the complexity of information, and the competitive environment in which libraries were no longer the only providers of information 15 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature identified that issues regarding the lack of support from the parent bodies are mainly in terms of provision of technical infrastructures for social media. Edewor and Okite-Amughoro (2016) found issues of poor infrastructure such as unavailability of internet access in campuses as a setback in social media usage in some academic libraries in Africa. They also identified infrastructural issues such as lack of maintenance culture, unreliable power supply, lack of staff training and government intervention, and the absence of marketing plan.…”
Section: Occurrences Of Distress Associated With Social Media In Acadmentioning
confidence: 99%
“…They are useful in broadening the horizon of users in their choice of relevant information sources and services. However, other researchers such as Edewor et al (2016) looked at marketing strategies used by some university libraries in Africa. The study identified the most frequently adopted marketing strategies in academic libraries in those libraries as flyers, handbills, leaflets, bulletins, newsletters and orientation programmes.…”
Section: Introductionmentioning
confidence: 99%